Same Day Surgical Intervention Dramatically Minimizes Complication Occurrence and Optimizes Perioperative Outcomes for Central Cord Syndrome. Issue 8 (October 2021) - Bortz, Cole; Dinizo, Michael; Kummer, Nicholas; Brown, Avery; Alas, Haddy; Pierce, Katherine E.; Janjua, Muhammad B.; Park, Paul; Wang, Charles; Jankowski, Pawel; Hockley, Aaron; Soroceanu, Alex; et al.
Abstract : Study Design: This was a retrospective cohort study. Objective: The aim of this study was to investigate associations between time to surgical intervention and outcomes for central cord syndrome (CCS) patients. Background: As surgery is increasingly recommended for patients with neurological deterioration CCS, it is important to investigate the relationship between time to surgery and outcomes. Materials and Methods: CCS patients were isolated in Nationwide Inpatient Sample database 2005−2013. Patients were grouped by time to surgery: same-day, 1-day delay, 2, 3, 4−7, 8−14, and >14 days. Means comparison tests compared patient factors, perioperative complications, and charges across patient groups. Controlling for age, comorbidities, length of stay, and concurrent traumatic fractures, binary logistic regression assessed surgical timing associated with increased odds of perioperative complication, using same-day as reference group. Results: Included: 6734 CSS patients (64% underwent surgery). The most common injury mechanisms were falls (30%) and pedestrian accidents (7%). Of patients that underwent surgery, 52% underwent fusion, 30% discectomy, and 14% other decompression of the spinal canal. Breakdown by time to procedure was: 39% same-day, 16% 1-day, 10% 2 days, 8% 3 days, 16% 4−7 days, 8% 8−14 days, and 3% >14 days. Timing groups did not differ in trauma status at admission, although age varied: [minimum: 1 d (58±15 y), maximum: >14 d (63±13 y)]. Relative to other groups, same-day patients had the lowest hospital charges, highest rates of home discharge, and second lowest postoperative length of stay behind 2-day delay patients. Patients delayed >14 days to surgery had increased odds of perioperative cardiac and infection complications. Timing groups beyond 3 days showed increased odds of VTE and nonhome discharge. Conclusions: CCS patients undergoing surgery on the same day as admission had lower odds of complication, hospital charges, and higher rates of home discharge than patients that experienced a delay to operation. Patients delayed >14 days to surgery were associated with inferior outcomes, including increased odds of cardiac complication and infection.